Relationships Between Social Support and Academic Burnout Among Undergraduate Nursing Students - Rossa, Nikita; Mediawati, Ati Surya; Sriati, Aat (Universitas Malahayati, 2024)
ABSTRACT Academic burnout is defined as a persistent feeling of exhaustion caused by pressure during study, feelings of pessimism when performing tasks, and thoughts that continue to feel inadequate. One of the factors that can affect academic burnout is social support. Social support is the feeling that individuals feel loved, cared for, valued, and considered important by people who play a role in their lives. This study aims to determine the relationship between social support and academic burnout among undergraduate students of the Faculty of Nursing at Padjadjaran University. The research method used is the quantitative method with proportionate stratified random sampling. The samples taken in this study amounted to 258 students. The sample reported a high level of social support (60.5%) and moderate level of academic burnout (90.3%). Most respondents have a moderate level of exhaustion (60.5%) and low cynicism (72.9%), while in the dimension of reduced academic efficacy, the moderate and high categories are equal (49.6%). The results show social support is negatively correlated with academic burnout. However, the correlations identified were relatively weak. Another finding in this study is that there is a significant negative correlation between exhaustion and social support and a significant positive correlation between reduced of academic efficacy and social support. This means that social support has a role towards academic burnout in the exhaustion and reduced of academic efficacy dimensions. Future studies are expected to identify or explore other predictors of burnout, such as self-concept, role conflict and role ambiguity, and isolation, or identify ways to prevent and reduce burnout based on factors that have been identified in nursing students. Keywords: Academic Burnout, Nursing Students, Social Support